Optimising nitrogen use efficiency of prilled urea through integrated use of nano-ZnO and green manuring for better productivity, quality and nutritional status of Basmati rice crop - Baral, Kirttiranjan; Shivay, Yashbir Singh; Prasanna, Radha; Kumar, Dinesh; Srinivasarao, Cherukumalli; Mandi, Sunil; Nayak, Somanath; Reddy, Kadapa Sreenivasa (Frontiers in Sustainable Food Systems, 2024)
In agricultural systems, significant nitrogen (N) losses from traditional fertilizers pose risks to food security and economic stability. An emerging approach to mitigate these losses involves nanoparticles (NPs) coatings onto urea, aiming to enhance N availability and consequently boost crop yields. To explore the most effective and sustainable N management strategies, a field experiment was carried out in Basmati rice at the ICAR-Indian Agricultural Research Institute, New Delhi, India over 2020–2021 in a split-plot design, with two summer green manure (GM) types-Sesbania (G2) and cowpea (G3) and fallow in the main plot and six nitrogen fertilization (NF) modules, i.e., 0 kg N + 5 kg Zn ha−1 through bulk ZnO (N1), N through prilled urea (PU) (N2), N through PU + 5 kg Zn ha−1 through bulk ZnO (N3), 1% bulk ZnO-coated urea (1% BZnCU) (N4), 0.1% nano ZnO-coated urea (0.1% NZnCU) (N5) and 0.2% nano ZnO-coated urea (0.2% NZnCU) (N6) in subplots replicated three times. The objectives of the study was to identify the optimal GM crops and the most effective NF modules on enhancing plant height, dry biomass, grain yield, milling quality, and N, P, K nutrition, as well as nitrogen use efficiency (NUE). Our findings demonstrated that, a significant enhancement in plant height (13.34%) and dry biomass (38.1%) at harvest was observed with the combined application of G2 and N6 when juxtaposed against G1 and N1. The pooled analysis revealed that GM enhanced grain yield by 12.75% in comparison to G1, irrespective of the NF modules employed. The Sesbania was identified as the top-performing GM, registering a yield 17.5% greater than fallow while it was 8.13% for cowpea. Among NF modules, there was a noted 10.03% yield increase when urea was zinc-coated compared to using only urea (N2), and a 33.75% increase against the N1. The application of N6 modules boosted hulling, milling, and head rice recovery by 3.73, 4.45, and 4.98%, respectively, compared to N1. Moreover, combining zinc with urea raised the N content in milled rice by approximately 9.1% and heightened the N, P, and K concentration in the straw by 22.8, 4.44, and 11.8%, and total N, P, and K uptake by 5.72, 3.33, and 11.7%, in comparison to the combined effect of N1 and N2. Considering the NUE metrics, such as partial factor productivity (PFP), agronomic efficiency (AE), recovery efficiency (RE), and physiological efficiency (PE), the application of GM showcased superior performance in PFP and RE against the G1, while AE and PE remained unaffected. The G2 as a GM, performed best in PFP and RE. The N5 module delineated the most substantial advancements in NUE indices, despite being comparable to N6. In conclusion, the adoption of Sesbania as a green manure crops, coupled with the 0.2% nano ZnO-coated urea module, is identified as an efficient method for maximizing growth, yield, milling attributes, nutrient assimilation, and overall NUE in the Basmati rice.